'No longer clad in corduroy'? The Glasgow University Irish National Club, 1907–1917. (October 2020) - Catháin, Máirtin Ó
Abstract : Unique among university clubs in Britain, the Glasgow University Irish National Club emerged before the first world war among mainly second generation, Scots-born Irish students to assist in the campaign for Irish home rule. It was a useful adjunct to the home rule movement and helped the Irish and mainly catholic students at the university carve out a niche for themselves firstly within the institution and thereafter in wider society. This reflected a growing Irish catholic middle class desirous of playing a greater role in Scottish public life during a time of great transition for the Irish in Scotland.